Current status of the application of gene editing in pigs - Fuminori TANIHARA; Maki HIRATA; Takeshige OTOI (The Society for Reproduction and Development, 2021)
Genetically modified animals, especially rodents, are widely used in biomedical research. However, non-rodent models are required for efficient translational medicine and preclinical studies. Owing to the similarity in the physiological traits of pigs and humans, genetically modified pigs may be a valuable resource for biomedical research. Somatic cell nuclear transfer (SCNT) using genetically modified somatic cells has been the primary method for the generation of genetically modified pigs. However, site-specific gene modification in porcine cells is inefficient and requires laborious and time-consuming processes. Recent improvements in gene-editing systems, such as zinc finger nucleases, transcription activator-like effector nucleases, and the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein (CRISPR/Cas) system, represent major advances. The efficient introduction of site-specific modifications into cells via gene editors dramatically reduces the effort and time required to generate genetically modified pigs. Furthermore, gene editors enable direct gene modification during embryogenesis, bypassing the SCNT procedure. The application of gene editors has progressively expanded, and a range of strategies is now available for porcine gene engineering. This review provides an overview of approaches for the generation of genetically modified pigs using gene editors, and highlights the current trends, as well as the limitations, of gene editing in pigs.